Superspace type II 4D supergravity from type II superstring - Nedel, Daniel [UNESP] (Sissa Medialab Srl, 2004)
We derive the equations of motion of type II 4D supergravity in superspace. This is achieved by coupling the Type II Berkovits’ hybrid superstring to an N 2 curved background and requiring that the sigma-model has N=(2,2) superconformal invariance at one loop. We show that there are no anomalies in the fermionic OPE’s and the complete set of compensator’s equations is derived from the energy-momentum tensor. The equations of motion describe a hypertensorial and vectorial multiplet coupled to a U 1 U 1 N 2 Poincarè Supergravity.